2017
DOI: 10.1111/fcsr.12245
|View full text |Cite
|
Sign up to set email alerts
|

Using Demographic Variables to Understand Body Size Perception and Implications for Retailers

Abstract: The purpose of the study was to identify demographic variables associated with women's body mass index (BMI) and body size perceptions and to determine if BMI affects body size perception. SizeUSA data (n = 6,811) were used for the data analysis. A multinomial regression between demographic variables, BMI, and body size perception showed that each demographic variable was a significant predictor of a women's BMI and body size perception. Results can be used to understand the BMI and body size perceptions of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Body image perceptions may be influenced by many factors including demographics (Alexander, Pisut, & Ivanescu, 2017). Demographics are defined as characteristics of people that include age, race, income, and educational level (Alexander et al, 2017). Alexander and colleagues examined body image perception and BMI among women and found that AA women were more likely to underestimate their weight than others.…”
mentioning
confidence: 99%
“…Body image perceptions may be influenced by many factors including demographics (Alexander, Pisut, & Ivanescu, 2017). Demographics are defined as characteristics of people that include age, race, income, and educational level (Alexander et al, 2017). Alexander and colleagues examined body image perception and BMI among women and found that AA women were more likely to underestimate their weight than others.…”
mentioning
confidence: 99%